Landscape fragility and visual quality in coastal areas: Assessment in the Tortugas resort – Casma, Peru. - Hurtado-Gutierrez, Camila Elizabeth; Montesinos-Linares, Alexia Lailyn; Cruzado-Palacios, María Delia; Flores-Idrugo, Eddier Albino (LACCEI, 2025)
Coastal tourist landscapes face increasing urban pressures that affect their scenic and ecological value. This research analyzed the landscape of the Tortugas resort in Casma, Peru, through the year 2025 using three articulated approaches. First, visual fragility was assessed to identify areas vulnerable to human intervention or natural processes. Second, visual quality was measured using perceptual and physical indicators, considering both observers’ perceptions and the tangible characteristics of the environment. Finally, the relationship between both variables was evaluated to understand how landscape vulnerability affects its visual appreciation. The methodology was quantitative, descriptive, and non-experimental, applying cartographic analysis, direct observation records, and surveys. The results showed an inverse relationship: areas with high visual fragility presented low levels of visual quality, reflecting a progressive loss of landscape value in the face of unplanned urban growth. It is concluded that it is essential to incorporate landscape criteria into land use planning to preserve the visual and environmental integrity of the resort and promote its long-term sustainability.